Jazz Elements within a Classical Framework: A Structural and Stylistic Analysis of Kapustin’s Variations, Op. 41 (Journal of educational development exploration, 2026)
Nikolai Kapustin’s works are often described as “sounding like jazz, yet being entirely written-out classical music.” This characterization is especially apt in the case of Variations, Op. 41. Composed in 1984, the work adopts variation form as its external framework while continuously drawing on the vocabulary of jazz piano in its rhythm, harmony, bass organization, and textural treatment. Based on the score, this article presents a sectional analysis of the structural relationships among the introduction, theme, and six variations, and further examines how elements such as swing, bebop, walking bass, comping, and ragtime are realized in specific measures. It argues that the most compelling aspect of this work lies not in a superficial juxtaposition of “classical plus jazz,” but in Kapustin’s genuine integration of jazz syntax into the process of variation. The development of motives, the shifting of tonal centers, and the reconfiguration of tempo and meter all interact with jazz-inflected sonorities, ultimately producing a piano work that is both formally rigorous and rich in the illusion of improvisation.
Keywords: Kapustin; Variations, Op. 41; Variation form; Jazz style; Piano writing